Relationships between dietary intakes of children and their parents: a cross‐sectional, secondary analysis of families participating in the Family Diet Quality Study. Issue 5 (1st August 2014) - Robinson, L. N.; Rollo, M. E.; Watson, J.; Burrows, T. L.; Collins, C. E.
Abstract: Background: Being overweight and obese in Australian children is common. Current evidence related to parental influence on child dietary intake is conflicting, and is particularly limited in terms of which parent exerts the stronger relationship. The present study aimed to assess mother–father and parent–child dietary relationships and to identify which parent–child relationship is stronger. Methods: A cross‐sectional analysis was performed of dietary intake data from 66 families with one parent and one child aged 8–12 years who were participating in the Family Diet Quality Study, in the Hunter and Forster regions of New South Wales, Australia. Dietary intakes were assessed using adult and child specific, validated semi‐quantitative 120‐item food frequency questionnaires. Diet quality and variety subscores were assessed using the Australian Recommended Food Scores for adults and children/adolescents. Pearson's correlations were used to assess dietary relationships between mother–father, father–child and mother–child dyads. Results: Weak‐to‐moderate correlations were found between mother–child dyads for components of dietary intake ( r  =   0.27–0.47). Similarly, for father–child dyads, predominantly weak‐to‐moderate correlations were found ( r  =   0.01–0.52). Variety of fruit intake was the most strongly correlated in both parent–child dyads, with the weakest relationships found for fibre (g 1000 kJ –1 ) in father–child and percentage energy from total fats for mother–child dyads. Mother–father dyads demonstrated mostly moderate‐to‐strong correlations ( r  =   0.13–0.73), with scores for condiments showing the weakest relationship and vegetables the strongest. For all dyads, strong correlations were observed for overall diet quality ( r  = 0.50–0.59). Conclusions: Parent–child dietary intake is significantly related but differs for mother versus fathers. Further research is required to examine whether differing dietary components should be targeted for mothers versus fathers in interventions aiming to improve family dietary patterns.